Pengaruh Experiential Marketing Terhadap Customer Loyalty (Survei Pada Konsumen Grab-Car di Kota Batam) - Arianis Chan; Nindi Atikah Safira; Rivani Rivani; Nurillah Jamil Achmawati Novel (Jurnal Sekretaris dan Administrasi Bisnis, 2021)
This research aims to find out about experiential marketing and customer loyalty as well as the effect of experiential marketing on customer loyalty in Grab-Car services.The objects examined in this study is experiential marketing and customer loyalty. The research method that used in this research is descriptive verification analysis and the design of research is survey. The sampling technique that used is non- probability sampling and done by using pusposive sampling. This research used simple linear analysis to determine the effect of experiential marketing on customer loyalty in Grab-car services. Data sourced from literature study, observation, questionnaire and interview. The population of this research is all Grab-Car consumers in Batam City. The sampling technique that used is non-probability sampling and done by using purposive sampling with the criteria of respondents is already using Grab-Car service in Batam City at least two times. The number of samples from this study was determined using iteration techniques with the acquisition of a sample size of one hundred thirty six respondents. The results of this research shows that experiential marketing has a significant effect on customer loyalty Grab-Car services, which means that any increase in experiential marketing will cause an increase in customer loyalty. The author suggested is that Grab-Car makes think marketing strategies more attractive so that consumers can think deeper so they can provide a good opinion of the company’s services. Keywords : Marketing, Experiential Marketing, Customer Loyalty